Branch capture reactions: displacers derived from asymmetric PCR. - Wong, D M (1991)
Branch capture reactions (BCR) contain three DNA species: (i) a recipient restriction fragment terminating in an overhang, (ii) a displacer strand containing two adjacent sequences, with one complementary to the overhang and to contiguous nucleotides within the recipient duplex and (iii) a linker which is complementary to the second displacer sequence. Branched complexes containing all three species may be captured by ligation of the linker to the recipient overhang. The use of 5-MedC in the displacer facilitates BCR. High temperature ligation with a thermostable enzyme increased specificity for ligation to the correct recipient in a complex mixture of restriction fragments. Displacer synthesis by PCR permitted separate reactions of formation of stable displacement complexes and of high-temperature ligation. Ethylene glycol-containing buffer permitted PCR with 5-MedCTP or high G + C products using thermostable polymerases. BCR may be used to modify the ends of one recipient DNA duplex in a population of duplex DNA fragments. Modification of the recipient could be used to facilitate detection, affinity chromatography or cloning. By using PCR to obtain a BCR displacer, the sequence non-homologous to the recipient duplex may be expanded to include the sequence of a selectable marker, thus facilitating chromosome walking.